The role of small woodland remnants on ground dwelling insect conservation in Chaco Serrano, central Argentina - Moreno, Maria Laura (2013)
Most terrestrial ecosystems are changing due to extensive land use, with habitat fragmentation being a major threat to biodiversity. We studied the effects of patch size, isolation and edge/interior localization on the ground dwelling insect communities associated to Chaco Serrano woodland remnants, in central Argentina. Sampling was carried out in December 2003 and March 2004 in nine remnants (0.57-1000ha) using pitfall traps. In total, 7071 individuals representing 12 orders and 79 families were recorded. The taxonomic composition of these communities was linked to remnant size. Insect abundance increased (as did their richness, albeit marginally) as remnant area decreased, with no significant effects of isolation or edge/interior localization on abundance, richness or diversity. No differential area effects were observed when abundance and richness of predators, scavengers and herbivores were compared. Thus, ground insect communities in fragmented Chaco Serrano seem to respond mainly to patch level, rather than to within-patch (edge effects) or landscape (isolation) level variables. Our results suggest that small Chaco Serrano remnants, by supporting larger ground-dwelling insect assemblages, may play an important role from a conservation viewpoint.